The Activity Of Cellulose Enzyme From Indigenous Bacteria "Bacillus Sp YLB1" As Bioactivator - Yunilas .; Lili Warly; Yetti Marlida; Irsan Riyanto (Jurnal Peternakan Integratif, 2019)
This study aims to test the activity of cellulase enzyme (CMCase) from indigenous bacteria "Bacillus Sp YLB1" as bioactivator of palm oil based feed. The treatment consists of various combinations of substart (feed), namely: P1 = 80% palm leaves + 10% palm kernel cake + 10% sludge; P2 = 60% palm leaves + 20% palm kernel cake + 20% sludge and P3 = 60% palm leaves + 30% palm kernel cake + 30% sludge. The parameters observed were cellulase enzyme activity (CMCase) on various combinations of palm oil waste and fermentation time. The results showed that cellulase enzyme (CMCase) production of Bacillus sp YLB1 bacteria during fermentation fluctuated ie 0.143 Units / ml; 0.372 Units / ml; 0.588 Units / ml; 1.013 Units / ml; 0.906 Units / ml; 1,065 Units / ml and 1,198 Units / ml.The activity of cellulase enzyme (CMCase) on substrate P1 (0.460 Unit / ml) is lower than P2 (0.897 Unit / ml) and P3 (0.908 Units / ml). From the results of this study can be concluded that cellulase enzyme activity indigenous bacteria Bacillus sp YLB1 influenced by the combination of substrate and fermentation time. The P3 substrate fermented with Bacillus sp YLB1 for 7 days gave a more optimal result than the other treatments.   Keywords: Cellulase enzyme, indigenous bacteria, substart (feed)